Study of the effect of combined reinforcement and modification of epoxy resin with rubbers on the impact strength of carbon fiber-reinforced plastic - Meiirbekov, M; Ismailov, M.B.; Kenzhegulov, A.K.; Mustafa, L.M.; Tashmukhanbetova, I.B. (Eurasian Journal of Physics and Functional Materials, 2026)
The effect of modified epoxy resin with polyurethane, silicone, and butadiene rubber and combined reinforcement with fiberglass and Kevlar on the strength properties of carbon fiber-reinforced plastic was studied. It was found that when rubber is introduced into the composition of the epoxy resin, polyurethane, and combined reinforcement according to the carbon fiber/Kevlar scheme in a ratio of 10:10 leads to an increase in impact strength by 42% to 273 kJ/m2 and compressive strength increases by 35% to 575 MPa Recommended Citation Meiirbekov, M. N.; Ismailov, M. B.; Kenzhegulov, A. K.; Mustafa, L. M.; and Tashmukhanbetova, I. B. (2024) "Study of the effect of combined reinforcement and modification of epoxy resin with rubbers on the impact strength of carbon fiber-reinforced plastic," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 1, Article 3. DOI: https://doi.org/10.32523/ejpfm.2024080103